Creating Singapore’s longest monthly rainfall record from 1839 to the present - GAO, Elaine (Institutional Knowledge at Singapore Management University, 2018)
Currently,the identification of decadal variability is limited by the lack of long-termmeteorological datasets; Singapore’s reliable contemporary network of automaticmeteorological stations (AWS) provides only about 30 years of rainfall data for thewhole island. In this study, rainfall data, sourced fromhistorical archives and recording monthly rainfall pre-dating the start ofofficial MacRitchie observations, are compiled from various locations acrossthe island. By making use of the contemporary AWS network, we evaluate thespatial relationship of rainfall between the historical sites and the currentMacRitchie site. This enables us to reconstruct historical rainfall atMacRitchie using the archive data, thereby building a single-location extendedrainfall record (though discontinuous) from 1839-present.